Analisis keterkaitan antara kedisiplinan guru dan prestasi belajar siswa di MTs Almaarif 01 Singosari - Kurniawan, Muchammad Akbar; Pradana, Frengky (Maliki Interdisciplinary Journal, 2024)
The importance of developing quality human resources as a response to modernisation and global competition is realised through formal, non-formal and informal education. Law No. 20/2003 on the National Education System affirms the vision of realising a strong education system. Teachers have a major role in shaping quality human resources by carrying out moral, educational, societal and scientific responsibilities. Teacher discipline is key in motivating students, shaping character and creating a conducive learning environment. Teachers must also demonstrate their moral commitment, devote themselves solely to God, and not expect material rewards. Teacher discipline is reflected in improving teaching skills, innovating learning methods, as well as attention and guidance to students. Disciplined teachers can be role models for students, encouraging them to develop strong character. Teacher discipline has a far-reaching impact, not only on individual success in teaching, but also on the progress of educational institutions and the social development of students. Therefore, it is important for teachers to understand their roles and responsibilities and perform their duties with high moral awareness and integrity.